Polymer modified-natural bitumen thermal aging resistance studies. Issue Volume 20:Issued 10(2019) (3rd October 2019) - Olabemiwo, Ojeyemi M.; Esan, Akintomiwa O.; Bakare, Hassan O.; Agunbiade, Foluso O.
Abstract: Bitumen is used as a binder in flexible road pavement but it reacts with atmospheric oxygen and hardens leading to road failures. This study therefore investigates the viability of using some polymers/modifiers to modify Agbabu natural bitumen (ANB) to reduce its susceptibility to oxidation and hence gives its road pavement longer service life. Purified ANB (base) sample was modified using melt blend technique. Three polymers: High-Density Polyethylene (HDPE), Poly(ethylene-co-vinyl-acetate) (PEVA) and Poly(styrene-co-butadiene) (PSCB) were used in 2, 4, and 6wt% for modification. Thereafter, long-term aging was thermally simulated on the base and polymer modified ANB samples at 60 oC. Both aged and unaged samples were then subjected to Fourier Transform Infrared (FTIR) Spectrometric Analysis and Oscillating Disc Rheometer (ODR) test to study the effects of aging on physicochemical and rheological properties of the samples. Our finding showed that PEVA modified samples at 2 and 6wt.% showed comparatively, improved resistance to fatigue cracking and rutting. However, the three modifiers used are capable of reducing the rate of thermal aging of the base sample.